A New Method for the Selective Removal of Cadmium and Zinc Ions from Aqueous Solution by Modified Clinoptilolite - Saeed Hajialigol; M.A. Taher; A. Malekpour (Adsorption Science & Technology)
Natural and modified clinoptilolite were used to remove zinc and cadmium ions from aqueous solution. The raw material was characterized by XRD and XRF analysis. Clinoptilolite was modified with benzyldimethyltetradecylammonium chloride (BDTA) to increase the adsorption of neothorin [2-(2-arsenophenylazo)chromotropic acid disodium salt, C 10 H 11 AsN 2 Na 2 O 11 S 2 ]. All experiments were undertaken using a continuous method. The ultimate goal of these studies was the selective removal of trace amounts of Cd(II) and Zn(II) ions from aqueous solution using a modified form of clinoptilolite. The results obtained showed that Cd(II) and Zn(II) ions were adsorbed quantitatively onto modified clinoptilolite over the respective pH ranges of 4.0–5.4 and 3.3–4.5. The influence on the adsorption process of various parameters such as the ionic concentration, the flow rate, the particle size, the pH value and the presence of other cations was studied to obtain the optimum conditions. Although clinoptilolite and its surfactant-modified form were not capable of the selective adsorption of the cations studied, on the basis of the results obtained it was possible to selectively remove Zn(II) and Cd(II) ions from aqueous solution by modified clinoptilolite using a two-step process, i.e. initial treatment with BDTA followed by treatment with neothorin.